2009
DOI: 10.1371/journal.ppat.1000313
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Reversal of Intrahepatic HCV-Specific CD8 T Cell Exhaustion by Combined PD-1/CTLA-4 Blockade

Abstract: Viral persistence is associated with hierarchical antiviral CD8 T cell exhaustion with increased programmed death-1 (PD-1) expression. In HCV persistence, HCV-specific CD8 T cells from the liver (the site of viral replication) display increased PD-1 expression and a profound functional impairment that is not reversed by PD-1 blockade alone. Here, we report that the inhibitory receptor cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) is preferentially upregulated in PD-1+ T cells from the liver but not bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
315
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(334 citation statements)
references
References 54 publications
(100 reference statements)
13
315
2
4
Order By: Relevance
“…Moreover, PD-1 blockade seems to reactivate effector T cells through the targeting of certain transcriptional factors (i.e., nuclear factor kappa-light-chainenhancer of activated B cells, interferon regulatory factors 1 and 2, orphan nuclear receptor NR4A1, and B-lymphocyte-induced maturation protein 1) that cause a reengagement of the effector mechanisms in the epigenome of exhausted T cells 59 . CTLA-4 has also been found to have a clear role in multiple chronic infections, including HBV, HCV, and HIV, and its inhibition can increase the function of pathogen-specific T cells 60,61 . Epigenetic and transcriptional mechanisms determine the functional plasticity of T cells to switch between their exhausted and effector states 62 , and so altering the transcriptional landscape-for example, by manipulating transcription-factor and gene-enhancer expression-and epigenetic landscape-for example, by manipulating the activity of histone-modifying methylation or demethylation enzymes, histone acetylases, and DNA demethylases-of adoptively transferred T cells may yield a more specific anti-tumor response than generalized PD-1 and CTLA-4 blockade.…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…Moreover, PD-1 blockade seems to reactivate effector T cells through the targeting of certain transcriptional factors (i.e., nuclear factor kappa-light-chainenhancer of activated B cells, interferon regulatory factors 1 and 2, orphan nuclear receptor NR4A1, and B-lymphocyte-induced maturation protein 1) that cause a reengagement of the effector mechanisms in the epigenome of exhausted T cells 59 . CTLA-4 has also been found to have a clear role in multiple chronic infections, including HBV, HCV, and HIV, and its inhibition can increase the function of pathogen-specific T cells 60,61 . Epigenetic and transcriptional mechanisms determine the functional plasticity of T cells to switch between their exhausted and effector states 62 , and so altering the transcriptional landscape-for example, by manipulating transcription-factor and gene-enhancer expression-and epigenetic landscape-for example, by manipulating the activity of histone-modifying methylation or demethylation enzymes, histone acetylases, and DNA demethylases-of adoptively transferred T cells may yield a more specific anti-tumor response than generalized PD-1 and CTLA-4 blockade.…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…PD-1 has been identified as a major cell-surface inhibitory receptor capable of regulating CD8 + and CD4 + T cell exhaustion in mice, as well as in humans and nonhuman primates (50). Tim-3 and CTLA-4 were recently found to be overexpressed on HIV-and hepatitis C virus-specific CD8 + and CD4 + T cells and to act to suppress effector functions of activated T cells (11)(12)(13)51). Upregulation of LAG-3 was also shown to correlate with the impaired effector functions and exhaustion of CD8 + T cells (10,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these inhibitory receptors, it was demonstrated that a variety of other inhibitory receptors were expressed on exhausted CD8 + T cells in chronic virus infections, and the increased levels of expression were critically associated with the severity of infection and the lower functionality of CD8 + T cells (10). Although the precise inhibitory mechanisms of each individual pathway are unclear, some inhibitory receptors, such as Tim-3, LAG-3, and CTLA4, are known to negatively regulate CD8 + T cell function cooperatively with PD-1, because combined blockade of these inhibitory receptors, along with the PD-1/PD-L1 pathway, synergistically improved CD8 + T cell responses (10)(11)(12)(13). Based on the present observations, Ag-specific effector CD8 + T cells in FV-infected mice seemed to be undergoing unusually rapid and extremely severe exhaustion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest evidence that exhausted cells retain the ability to mount a potent effector response comes from the many studies in which strong anti-tumor or anti-viral immunity could be restored by blocking PD-1/PD-L1 interaction alone or in combination with targeting other receptors [46][47][48][49][50][51][52] . This approach of antibody-mediated "checkpoint blockade" is now increasingly used to treat patients with cancer and its impact on chronic infections in humans is being evaluated (Box 1).…”
Section: Evidence That Functional T-cells Are Maintained In Chronic Imentioning
confidence: 99%